2023
DOI: 10.3390/clockssleep5020019
|View full text |Cite
|
Sign up to set email alerts
|

Shift Happens: Emergency Physician Perspectives on Fatigue and Shift Work

Abstract: Research has shown that shiftworkers experience poor sleep and high levels of fatigue. Although considerable research has been performed on fatigue within many shift-work occupations, very little has been done with emergency physicians (EPs). This qualitative study was conducted with the goal of gaining insight into EPs’ perceptions of fatigue at work. Twenty EPs from an academic medical center participated in virtual interviews, with nine open-ended questions asked in a semi-structured interview format. Twelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Physicians may underreport their feelings of fatigue because of professional and social pressures. Moreover, self-reported fatigue does not necessarily correlate directly with decision quality, making it important to consider it in conjunction with other forms of evidence [9,26].…”
Section: Self-reported Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Physicians may underreport their feelings of fatigue because of professional and social pressures. Moreover, self-reported fatigue does not necessarily correlate directly with decision quality, making it important to consider it in conjunction with other forms of evidence [9,26].…”
Section: Self-reported Fatiguementioning
confidence: 99%
“…Physician burnout: Chronic exposure to decision fatigue can contribute to physician burnout, with an incidence of 25-78% [ 3 ]. The cumulative stress of high-stakes decision-making in a high-stress environment may result in emotional exhaustion, depersonalization, and reduced personal accomplishment [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…This finding was echoed in a more recent meta-analysis highlighting that burnout was most strongly associated with emergency medicine and intensive care physicians, while the lowest association was found among general practitioners ( 34 ). Some attribute the higher risk of burnout among emergency medicine physicians to certain working conditions such as schedules that disrupt natural circadian rhythms, workload unpredictability and the exposure to trauma and human suffering ( 35 , 36 ). In contrast, the American Medical Association’s Organizational Biopsy 2022 found that both emergency medicine (62%) and family medicine (58%) were specialties with the highest percentage of physician burnout ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emergency physicians are susceptible to negative outcomes like burnout, decision fatigue and a higher staff turnover. 1 The coronavirus disease 2019 (COVID-19) has further exposed the gap in ED with a surge of patients, shortage of healthcare providers, and higher risk of infection among frontline workers. 2 Decision fatigue among EPs is not uncommon and is associated with an increased risk of impaired clinical-decision making, inadequate treatment plans, medication errors, and inappropriate patient disposition.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the patient volumes, acuity, and arrival times, the ED workload may change rapidly. 1 The studies reported an altered cognitive ability, decline in short-time memory, and disturbed sleep among EPs because of the shifting nature of their work, making them more prone to errors in decision-making. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%